The factors influencing on employees transfer of training at The New Straits Times Press Bhd (NSTP) Bangsar / Nurul Farhana Hambali - Hambali, Nurul Farhana (2010)
Transfer of training is an important human resource development (HRD) issue with respect to linking individual change to the requirements of the organizational system. The discussion on the transfer of training concepts has been an ongoing issue among human resource management practitioners and educationists. The researcher wants to look into whether participants of training program are able to transfer and apply the skills they learn to their work. The main objective of this research is to identify the main factor that influences transfer of training at The New Straits Times Press (Malaysia) Bhd (NSTP). The second objective is to examine the relationship between the factors towards transfer of training. The factors are trainee characteristics, training design and work environment. Researcher used questionnaire as a main tools in data collection method. A total of 65 sets of questionnaire have been successfully collected back from the respondent. Once the data have been collected, it will be analyzed using Statistical Package for Social Sciences (SPSS) version 14 to find out the frequency, percentage, mean and Pearson Correlation. As a result, with the both objectives stated, all independent variables have a positive relationship towards transfer of training.